In the Shadow of the Past: The Literary Representation of the Grandchildren of the War as “Nebelkinder” - Wolting, Monika (Porównania, 2025)
This study analyzes Nebelkinder – grandchildren of the war – through Draesner and Gregg’s works. It reveals how war children’s silence about trauma profoundly affected their descendants. Key aspects include transgenerational trauma transmission, absent family narratives, and “fog” metaphors symbolizing emotional confusion. The polyphonic narrative technique portrays complex psychological processes from multiple perspectives. Focus lies on psychosomatic effects of inherited trauma on war grandchildren. The literary texts provide crucial insights into trauma transmission dynamics and emphasize the necessity of intergenerational dialogue. The absence of family history and mementos affects the identity formation of the younger generation. These works are significant for understanding psychosocial phenomena in post-war German history, breaking silence and fostering cross-generational healing processes.